Tissue-specific parameters for the design of ECM-mimetic biomaterials. (15th September 2021) - Tonti, Olivia R.; Larson, Hannah; Lipp, Sarah N.; Luetkemeyer, Callan M.; Makam, Megan; Vargas, Diego; Wilcox, Sean M.; Calve, Sarah
Abstract: The extracellular matrix (ECM) is a complex network of biomolecules that mechanically and biochemically directs cell behavior and is crucial for maintaining tissue function and health. The heterogeneous organization and composition of the ECM varies within and between tissue types, directing mechanics, aiding in cell-cell communication, and facilitating tissue assembly and reassembly during development, injury and disease. As technologies like 3D printing rapidly advance, researchers are better able to recapitulate in vivo tissue properties in vitro ; however, tissue-specific variations in ECM composition and organization are not given enough consideration. This is in part due to a lack of information regarding how the ECM of many tissues varies in both homeostatic and diseased states. To address this gap, we describe the components and organization of the ECM, and provide examples for different tissues at various states of disease. While many aspects of ECM biology remain unknown, our goal is to highlight the complexity of various tissues and inspire engineers to incorporate unique components of the native ECM into in vitro platform design and fabrication. Ultimately, we anticipate that the use of biomaterials that incorporate key tissue-specific ECM will lead to in vitro models that better emulate human pathologies. Statement of significance: Biomaterial development primarily emphasizes the engineering of new materials and therapies at the expense of identifying key parameters of the tissue that is being emulated. This can be partially attributed to the difficulty in defining the 3D composition, organization, and mechanics of the ECM within different tissues and how these material properties vary as a function of homeostasis and disease. In this review, we highlight a range of tissues throughout the body and describe how ECM content, cell diversity, and mechanical properties change in diseased tissues and influence cellular behavior. Accurately mimicking the tissue of interest in vitro by using ECM specific to the appropriate state of homeostasis or pathology in vivo will yield results more translatable to humans. Graphical abstract: Image, graphical abstract